Ensartinib for EML4-ALK-positive lung adenocarcinoma with comorbid mutations in TP53, EGFR, and ERBB2: a case report - Huang, Xiaoqing; Zhou, Lingxian; Xia, Jianyong; Jian, Haifeng; Liu, Jinji; Huang, Yunying; Chen, Qingsheng (Frontiers in Oncology, 2025)
BackgroundIn non-small cell lung cancer (NSCLC), anaplastic lymphoma kinase (ALK) gene rearrangements are commonly detected in lung adenocarcinoma. ALK-positive (ALK+) patients may occasionally exhibit concurrent genetic alterations that potentially impact prognosis. New therapeutic strategies are needed for ALK+ NSCLC patients with multiple simultaneous gene mutations.Case presentationA 58-year-old man was diagnosed with lung adenocarcinoma (stage IVB, T4N3M1c) with an echinoderm microtubule-associated protein-like 4-ALK+ (EML4-ALK+) rearrangement, harboring tumor protein 53 (TP53), epidermal growth factor receptor (EGFR), and receptor tyrosine-protein kinase erbB-2 (ERBB2) mutations. After three cycles of chemotherapy, the patient developed intolerance. Subsequently, ensartinib (225 mg daily) was administered orally on April 14, 2021. After 3 months of ensartinib treatment, the patient achieved a partial response and reached stable disease at six months, which sustained for 30 months till April 8, 2024, with grade 1 rash and no brain metastases. Currently, the patient remains on ensartinib treatment, without disease progression.ConclusionThis case demonstrates the potential for ensartinib in the treatment of EML4-ALK+ lung adenocarcinoma with multiple gene mutations. Further investigation through clinical trials is needed to evaluate the safety and efficacy of this targeted therapy.